Geochemical characteristics of the Shuanghu crystalline graphite deposit in East China: implications for original rocks, sedimentary environments and carbon sources - Liu, Feng; Rao, Wenbo; Zhang, Yangyang; Yao, Weijun; Shi, Lin; Xu, Mingzuan; Ren, Sipu; Li, Xiaohui; Li, Ziyi (Frontiers in Earth Science, 2025)
The Shuanghu crystalline graphite deposit, situated in the Sulu ultra-high pressure metamorphic belt, has received limited research attention. In this study, geochemical characteristics of this deposit were investigated to determine original rocks, sedimentary environments, carbon sources, and metallogenic processes. SiO2 (56.94%–72.84%) and Al2O3 (9.7%–13.29%) are enriched in graphite quartzite and granulite while CaO (21.89%–42.56%) and MgO (5.56%–18.4%) are enriched in (graphite-bearing) marbles. Ba and Nb are depleted to varying degrees in all rocks. In graphite quartzite and granulite, the Rb/Sr ratios are higher than the Sr/Ba ratios. All rocks are characterized by LREE enrichment and HREE depletion with negative Eu and Ce anomalies. The δ13C value of graphite in graphite quartzite (−31.2‰ to −30.2‰) is more negative than in graphite-bearing marble (−24.4‰ to −23.2‰) while the δ13C values of carbonates in (graphite-bearing) marbles approximate 0‰. The integrated geochemical data indicate initial deposition of this deposit occurred in coastal-neritic environments under oxygen-deficient conditions, with original rocks comprising argillaceous-sandy clastic rocks and carbonates. Carbon isotopic signatures suggest quartzite graphite originated solely from organic matter, whereas marble graphite resulted from a mixture of organic and minor carbonate-derived carbon. A three-stage metallogenic model for the Shuanghu crystalline graphite deposit was proposed: (1) late Proterozoic organic deposition, (2) Triassic metamorphic mineralization, (3) post-200 Ma tectonic activation. These findings enhance understanding of graphite genesis in the Sulu orogen and provides guidance for regional exploration strategies.